2023
DOI: 10.1039/d3nj01955a
|View full text |Cite
|
Sign up to set email alerts
|

Computational design of efficient near-infrared TADF emitters with hot-exciton characteristics

Abstract: Developing near-infrared (NIR) TADF emitters is challenging due to the inherent energy gap law. In this work, we designed a set of twelve donor-acceptor1-acceptor2 (D-A1-A2) type NIR pure organic emitter...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 78 publications
(101 reference statements)
0
5
0
Order By: Relevance
“…For designing OLED materials with computational means, the ability of calculating various transition rate coefficients can play an important role for both radiative and nonradiative decays, as the calculation can directly lead to property prediction such as the luminescence efficiency. Indeed, numerous studies have been reported for such calculations [119,[132][133][134][135], and similar studies may prove their utility, especially toward testing the hypotheses. Provided that there is still some room for practical improvements for the related formalisms as mentioned in Section 3.5, we expect that future methodology developments and computational studies based on them will provide valuable insights for designing hot exciton materials.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…For designing OLED materials with computational means, the ability of calculating various transition rate coefficients can play an important role for both radiative and nonradiative decays, as the calculation can directly lead to property prediction such as the luminescence efficiency. Indeed, numerous studies have been reported for such calculations [119,[132][133][134][135], and similar studies may prove their utility, especially toward testing the hypotheses. Provided that there is still some room for practical improvements for the related formalisms as mentioned in Section 3.5, we expect that future methodology developments and computational studies based on them will provide valuable insights for designing hot exciton materials.…”
Section: Discussionmentioning
confidence: 80%
“…Several papers reported predictions on the hRISC rates with the help of the thermal vibration correlation function (TVCF) formalism [117]. However, the IC rates were either not really compared to [102,118,119] or actually shown to be much faster than the hRISC rate [120]. Nevertheless, solid experimental evidence exists to show that the hot exciton materials bear preferable properties that cannot be explained through TADF and/or TTA mechanisms.…”
Section: Future Computational Prospects On Hot Exciton Materialsmentioning
confidence: 99%
“…Hot exciton emitters harness dark triplet excitons from higher-energy triplet states to radiative singlet states, effectively utilizing these triplet excitons through a fast nanosecond-scale RISC process. 56 Kasha's rule in photochemistry states that significant photon emission primarily originates from the lowest excited state of a given multiplicity. Certain materials exhibit distinctive electronic structures and energy level arrangements, hindering internal conversion from higher excited states (Hot-Excitons) to S 1 or T 1 and enabling direct photochemical processes, contrary to Kasha's rule.…”
Section: Hot-exciton Emittersmentioning
confidence: 99%
“…Consequently, there is a critical need to address the efficient utilization of dark triplet excitons. Hot exciton emitters harness dark triplet excitons from higher-energy triplet states to radiative singlet states, effectively utilizing these triplet excitons through a fast nanosecond-scale RISC process . Kasha’s rule in photochemistry states that significant photon emission primarily originates from the lowest excited state of a given multiplicity.…”
Section: Hot-exciton Emittersmentioning
confidence: 99%
See 1 more Smart Citation